Implementation framework of enterprise resource planning for small and medium enterprises in Northern States of Malaysia - Ang, Moon Thiak (2018)
ERP entails the managing and planning of company’s resources in the most productive, effectiveness and profitable manner. It allows companies to integrate their information and business processes in a predetermined manner to ensure profitability and efficiency. Although, successful ERP implementation comes with various business competitive advantages however; Small and Medium Enterprises (SMEs) are facing great difficulties and challenges in achieving successful ERP implementation compared with Large Enterprises (LEs). Thus, this thesis proposed ERP implementation framework for SMEs which can reduce high degree of complex organization changes and enhance successful ERP implementation. This study makes used qualitative one-on-one in-depth interview research design. There are sixty respondents for this study from five different positions such as I.T personnel, ERP constants/Project Manager, ERP users, top management and customers. Those sixty respondents are from twelve different companies within northern region of Malaysia. The gender disparity of 60% to 40% ratio of male to female respondents was observed. This depicts that most SMEs assigned key personnel positions to males compared with females on ERP administration. In addition, most of the respondents are first degree (BSc) holders making 90% while the other 10% are second degree (Masters) holders. The findings of this study identified eight CSFs and seven CFFs that influence successful implementation of ERP in SMEs. The study has been able to propose an ERP implementation framework specifically targeted at the SMEs. The framework strengthens the position of existing ERP implementation framework through explication of the importance of ERP implementation in SMEs. This study specifically argues that factors such as funding, time and customization are very imperative for the successful implementation of ERP in SMEs which are missing in many past studies.